Pengaruh Pastoral Sekolah bagi Pembinaan dan Pengembangan Iman Remaja SMPK di Kota Kefamenanu - Amsikan, Modesta (Kanisius, 2023)
The problem is how far this Pastoral School is implemented in Catholic junior high schools in the city of Kefamenanu? What is the influence of the Pastoral School on the development of a child's faith? This study uses a qualitative method. The research was conducted from 21 February to 5 March 2023. The respondents were a pastoral team and Catholic religion teachers at St. Francis Xavier Daughter, and St. Francis Xavier Catholic Middle School, who are actively involved in the school's pastoral assistance. Total respondents were 7 people from St. Francis Xavier Catholic Junior High School, 4 respondents and 3 respondents from St. Francis Xavier Catholic Junior High School. The definition of Pastoral School for the development of the faith of Catholic Junior High School children in the city of Kefamenanu is that the pastoral school is a place for fostering the faith of children in the school environment. Overall, namely 7 respondents (100%), were able to answer or define an understanding of the development of children's faith. In connection with the pastoral influence of schools for the development of children's faith in Catholic Junior High School -Kefamenanu city. Respondents could see the pastoral influence of the school on the development of a child's faith. The data shows that 85.71% of the respondents were able to see the influence of school pastoralism on the development of children's faith, besides that there was 1 respondent 14.28% said that school pastoralism had little impact on children's faith development because there were still many children who did not want to be involved in spiritual activities